Tracer Study of Bachelor of Science in Office Administration Graduates of Camarines Sur Polytechnic Colleges - Hallare, Syrell M.; Jintalan, Jocelyn O. (Journal of Management Studies and Development, 2025)
The research is primarily a tracer study of the Bachelor of Science in Office Administration graduates of Camarines Sur Polytechnic Colleges, S/Y 2017-2018. Specifically, it sought to answer the personal, professional, and employment profile of the respondents,  the graduates level of satisfaction on the services provided by CSPC, and the attributes that contributes to the employability of the graduates. It also identified the assessment of the employers on the job performance of the graduates. Moreover, this research proposes recommendations to improve the BSOA curriculum and enhance the employability of BSOA Graduates. Descriptive Method was used in this study. The respondents were the two hundred (220) BSOA graduates and some of the employers. The findings revealed that majority of the graduates are gainfully employed holding a permanent position in private organizations as an entry level/ rank and file employee. BSOA graduates are very satisfied with the educational services provided by CSPC such as the physical facilities, Student Workload, Teaching Strategies and Qualifications of Faculty. The attributes that contribute much to the employability of the graduates are Computer Literacy, Work Experience and Human Relation Skills while  Appearance, Entrepreneurship Skills and High Community and Family Involvement do not show much relevance in the employability of the graduates. The employers assessment on the performance of the graduates is perceived to be Excellent.